Towards Sustainable Innovation : A five step approach to sustainable change (2017)
This chapter provides a brief outline of the subject and the book’s content. The terms sustainability and innovation should not be considered separately, not only when talking about sustainable innovation. They are closely linked to one another. The main goal of sustainable innovations is to develop new products and technologies that have a positive impact on the company’s triple-bottomline. Thus, they have to be ecologically and economically beneficial as well as socially balanced. Thereby, they are strengthening a company´s market position. In doing so, companies focus their activities on the one hand on technological and innovative developments and, on the other hand on the wishes, expectations and problems of their customers.